The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5424/sjar/2013113-3531
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Presence, quantification and phylogeny of Israeli acute paralysis virus of honeybees in Andalusia (Spain)

Abstract: This study aimed to assess the possible relationship between the presence of Israeli acute paralysis virus (IAPV) of honeybees and disease symptoms development at the colony level, to describe the IAPV load in field colonies and to illustrate phylogenetic relationships between IAPV isolates in Andalusia (Spain). Presence and load of IAPV was studied in 96 colonies from all provinces in Andalusia. Epidemiological surveys were performed in all the colonies to assess their sanitary status. IAPV was found in 13.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The total absence of IAPV during the entire study suggests that the virus is not abundant in Spain, at least not in the province of Córdoba. The fact that we can exclude IAPV as a cause of the total loss and depopulation of several colonies during the study is reminiscent of our 2013 observation, also in Andalusia, that IAPV was not involved with colony collapse in that study (Vicente-Rubiano et al, 2013). Our results suggest that the association between IAPV and CCD observed in the USA (Cox-Foster et al, 2007; Maori et al, 2007) may not apply to southern Spain.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The total absence of IAPV during the entire study suggests that the virus is not abundant in Spain, at least not in the province of Córdoba. The fact that we can exclude IAPV as a cause of the total loss and depopulation of several colonies during the study is reminiscent of our 2013 observation, also in Andalusia, that IAPV was not involved with colony collapse in that study (Vicente-Rubiano et al, 2013). Our results suggest that the association between IAPV and CCD observed in the USA (Cox-Foster et al, 2007; Maori et al, 2007) may not apply to southern Spain.…”
Section: Discussionmentioning
confidence: 55%
“…It also damages honey bees indirectly by transmitting several viruses, including deformed wing virus (DWV), Kashmir bee virus (KBV), sacbrood bee virus (SBV), and Israeli acute paralysis virus (IAPV) (Kralj and Fuchs, 2006; Martin et al, 2012). Meta-genomic analysis has suggested that IAPV may cause CCD (Cox-Foster et al, 2007; Maori et al, 2007), but subsequent work in Spanish apiaries has called into question the link between IAPV and colony losses (Blanchard et al, 2008; Garrido et al, 2013; Vicente-Rubiano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…IAPV and SBV were not detected in any colony during the entire study. Although one study has associated IAPV with colony collapse disorder [41], more recent work in the same and other geographic areas as the present study suggests that this virus by itself is not a determinant in colony collapse [42].…”
Section: Discussionmentioning
confidence: 76%
“…Still, since many viral surveys in colonies around the world detected a substantial prevalence of IAPV in covert infections [16,24,25,28,30,36,38] we decided to study the status of this virus in the CCD colonies that we recovered. …”
Section: Discussionmentioning
confidence: 99%
“…Early-on we detected the presence of significant loads of IAPV in worker bees of these colonies. Given the fact that many viral surveys in colonies around the world pointed to a substantial prevalence of IAPV in covert infections [ 16 , 24 , 25 , 28 , 29 , 36 , 38 ], we decided to study the status of this virus in these CCD colonies. We rescued several of these clinical CCD-colonies, avoiding their immediate collapse, to test the hypothesis if IAPV was actively replicating in them and if the virus was infectious to healthy bees.…”
Section: Introductionmentioning
confidence: 99%